Copper-based opaque red glasses – Understanding the colouring mechanism of copper nanoparticles in archaeological glass samples - Druenert, F.; Blanz, Magdalena; Pollok, Kilian; Pan, Z.; Wondraczek, Lothar; Moncke, D. (Optical Materials, 2018)
Red opaque glasses of two different sites in central Germany, a medieval glassworks in Glashütten, Taunus Mountains, and an early modern glassworks in Wieda, Harz Mountains, were analysed with regard to their optical appearance. By scanning electron microscopy and X-ray diffraction, metallic copper nanoparticles were identified as a conspicuous constituent in these glasses. In addition, similar opaque red glasses were reproduced in the laboratory in order to better understand the manufacturing process. Detailed analysis of the optical scattering was conducted in order to evaluate the role of Cu0 nanoparticles in the colouring mechanism relative to other possible reasons of colouration. We find clear differences between the possible contributions of Cu2O (cuprite) particles and metallic copper (Cu0) nanoparticles. Through simulated backscattering spectra we were able to calculate an average copper particle radius in the archaeological glass samples resulting in a value of up to 95 nm, which matches well the results of SEM investigation (minimum 65 nm). Using the methods we applied in this study, it becomes possible to reconstruct various processing conditions as they were applied in medieval manufacture of these particular materials.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Copper nanoparticles; Copper ruby; Historical glass making practices; Medieval glasses; Mie-scattering; Opaque red glasses